Off-balance sheet and bank behavior: Does market power matter? - Ignatia Ryana Widyatini (Global Business & Finance Review (GBFR), 2024)
Purpose: This paper examines the significant effect of off-balance sheets (OBS) on earnings management in the banking industry in Indonesia. Furthermore, this study also examines the role of market power as a moderating variable that moderates the relationship between off-balance sheet activities and earnings management. Design/methodology/approach: The off-balance sheet is measured through loan commitment facilities by observing the unused commitment facilities. Moreover, earnings management is measured through discretionary loan loss provisions (DLLP) by seeing the policy management makes in forming loan loss provisions (LLP) as income reduc- tion accounts on the income statement. Multiple regression testing is used to measure the significant effect of off-balance sheet activities on discretionary behavior in LLP and the role of market power as a moderating variable. Findings: The study results show that off-balance sheet activity and market power are related to earnings management. Off-balance sheets have a positive effect on earnings management. Conversely, market power has a negative effect on earnings management. Another finding found that market power weakens the relationship between off-balance sheets and earnings management. Research limitations/implications: This research did not conduct an overall analysis of off-balance sheet exposure in banking financial statements. Thus, future research on total commitments and contingencies such as letters of credit and bank guarantees will be interesting to examine. Originality/value: Previous studies have observed LLP in earnings management and competition policies. However, they had not examined the relationship between the practice of earnings management through LLP toward off-bal- ance sheets and market competition. Therefore, the research gap will be discussed in this study. In addition, the research has two contributions, the first is related to earnings management literature in the banking industry and the second is to assess whether higher bank market power tends to influence earnings management practices through off-balance sheet activities.
Keywords: 650; Off-balance sheet; LLP; Market power